FAKTOR-FAKTOR KEPATUHAN MINUM OBAT ANTI TUBERCULOSIS PADA PENDERITA TB PARU - Sary, Annisa Novita; Putri, Riva Nadia; Marini, Nina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Tuberculosis is a major public health problem in Indonesia, ranked third most in the world with 110 per 100,000 people. The number of TB cases found and treated during 2022 in West Pasaman district of 410 cases. Puskesmas Ujung Gading is the most common case of pulmonary tuberculosis in Western Pasaman District of 63 cases (15.4%) of 410, and the number of incomplete treatment of 54.7%. The purpose of this study was to know the factors related to the compliance of drinking anti-tuberculosis drugs (OAT) in TB sufferers. The design of this research is a cross-sectional study design. The population in this study was all TB patients in the Puskesmas working area Ujung Gading of West Pasaman with the sampling technique of the total population of 53 samples. Data was computerized using Chi-Square statistical tests with a 95% confidence rate (α=0,05). The results showed that p-value = 0.013 (knowledge level) and p-value = 0.008 (family support). It can be concluded that there were a relationship of knowledge and family support with compliance of OAT drinking in TB sufferers in the Puskesmas Working Region End of Gading by 2023. It is hoped that Puskesmas can improve awareness about pulmonary tuberculosis to improve family knowledge and support to TB patients.Keywords: Compliance Anti-Tuberculosis Medicine,level of knowledge, family support